The impact of transfer pricing and thin capitalization on tax avoidance in the advertising, printing, media, wholesale trade, and production of goods listed on the Indonesia Stock Exchange during the 2020 – 2022 period - Genisa, Theresa Putri; imbolon, Richard Friendly (Universitas Wiralodra, 2023)
One of the revenues received by a country comes from tax payments. However, some people consider taxes a burden, which becomes a reason to engage in tax avoidance practices. This research aims to identify the impact of transfer pricing practices and minimal capital use on tax avoidance efforts in the advertising, printing, media, wholesale trade, and goods production subsectors during the 2020-2022 period. This quantitative research method collects secondary data from companies listed on the Indonesia Stock Exchange (BEI) annual reports. This data was obtained from official sources, including the company's official website and the IDX website, and succeeded in collecting a sample of 30 companies. Data was analyzed using multiple linear regression and IBM SPSS Statistics 25 software. The research results show that setting transfer prices and using minimal capital significantly influences tax avoidance efforts in the advertising, printing, media, wholesale trade, and goods production subsectors. Listed on the Indonesian Stock Exchange during the 2020-2022 period. These findings have important implications, emphasizing the importance for all parties concerned to comply with tax obligations without trying to avoid them.